Composition-dependent apparent activation-energy and sluggish grain-growth in high entropy alloys. Issue 7 (3rd July 2019) - Gwalani, B.; Salloom, R.; Alam, T.; Valentin, S. G.; Zhou, X.; Thompson, G.; Srinivasan, S. G.; Banerjee, R.
ABSTRACT: Experimental results reveal that the apparent activation-energy for grain-growth in an fcc- based Alx CoCrFeNi high entropy alloy (HEA) system increases from 179 to 486 kJ/mol when the Al content increases from x  = 0.1 to 0.3. These unexpectedly high apparent activation-energy values can be potentially attributed to solute clustering within the fcc solid-solution phase that develops with increasing Al content in this HEA. Detailed microstructural analysis using atom-probe tomography and density functional theory (DFT) calculations strongly indicate the presence of such nanoscale clusters. This phenomenon can change grain-growth from a classical solute-drag regime to a much more sluggish cluster-drag based mechanism in these HEAs. GRAPHICAL ABSTRACT: IMPACT STATEMENT: First report on a composition dependent change in apparent activation-energy for grain-growth in high entropy alloys. A novel cluster drag effect inhibiting grain-growth kinetics is suggested.